The incidence of gastritis in bariatric patients and therapy nutritional with functional foods in improving quality of life (Research, Society and Development, 2022)
Gastritis is a nonspecific term that literally means inflammation of the stomach and can be used to describe symptoms related to the stomach, endoscopic findings of the gastric mucosa or histological changes characterized by infiltration of inflammatory cells of the epithelium, such as polymorphonuclear cells (PMNs). With proper nutrition, the nutrients absorbed can treat gastritis, promote digestion, heal or relieve burning in the most vulnerable stomachs. The objective was to evaluate the incidence of gastritis in bariatric patients and the importance of nutritional therapy with functional foods in the recovery of the gastric mucosa and in the improvement of the quality of life. A bibliographic review was carried out based on the virtual libraries SciELO (Scientific Electronic Library Online), Pubmed (National Library of Medicine), government sectors such as MS (Ministry of Health), WHO (World Health Organization, scientific journals and books), with exploratory qualitative approach based on the authors' experience available in the scientific literature. The study shows that Helicobacter pylori infection occurs in 24-67% of bariatric patients. Upper digestive endoscopy (UGE) is used to investigate this bacterium in the preoperative period due to its high incidence and possible association with pathological abnormalities in the stomach. Nutritional therapy as well as caloric distribution adjusted to the patient's needs aims to normalize nutritional status and promote healing. In addition, it has been observed that a balanced diet is essential for the treatment of gastritis, as functional foods can prevent, treat and even alleviate the symptoms associated with the disease. However, there are few innovative works on functional nutritional therapy; therefore, further research is needed specifically addressing diet therapy for the treatment of gastritis.